Aerobic Rice - responding to water scarcity, An impact assessment of the ‘STAR in Asia’ project - Templeton, D.; Bayot, Ruvicyn S. (CGIAR Challenge Program on Water and Food, 2011)
Rice, a staple food for over 70% of Asians, is also the single biggest user of water, requiring 2-3 times more input (irrigation plus rain) water per unit of grain produced than crops such as wheat and maize. With growing populations, increased urbanisation and environmental degradation, the supply of fresh water is depleting. Recognising the water constraints to rice yield, the aim of the project entitled ‘Developing a System of Temperate and Tropical Aerobic Rice (STAR) in Asia’ was to develop water-efficient aerobic rice technologies. This paper highlights the success of that project.